Flexible Supercapacitors Based on CNT/MnO2-BP Composite Yarn Synthesized by In Situ Reduction. Issue 8 (19th August 2021) - Zhou, Qiang; Tang, Gongbin; Chen, Xiuhang; Su, Fenghua
Abstract : Solid-state flexible supercapacitors are considered significant prospective energy storage devices, and carbon nanotube (CNT) yarn is an ideal electrode material for constructing linear flexible supercapacitors because of its high electrical conductivity and flexibility. However, the relatively low specific capacitance and energy density of a supercapacitor made of pure CNT yarn limits its application. Here, we prepared a CNT/MnO2 -BP composite yarn via a facile one-step liquid deposition method by the innovative introduction of few-layer black phosphorous (BP) nanosheets. The redox reaction between the BP and the potassium permanganate forms MnO2 and an electrolyte of phosphorus acids (Hx POy ). The two-ply yarn supercapacitor composed of the CNT/MnO2 -BP composite yarn shows excellent electrochemical properties with a volumetric capacitance of 441.79 F cm −3 at the scanning rate of 0.01 V s −1 and an energy density of 9.82 mWh cm −3 at a power density of 441.79 mW cm −3 . Herein, this work provides a way to improve the electrochemical performance of CNT yarn-based supercapacitors that can act as flexible energy storage devices for wearable electronics.